Implementasi Aplikasi Papan Komunikasi (Communication Board) Berbasis Tablet Android Bagi Tunarungu - Moh. Abu Hasan; Herman Tolle; Adam Hendra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
One of the difficulties is how the deaf can inform the sign language used and can be understood by people who can hear so deaf people can communicate, interact, socialize, make friends, and dialogue occurs in everyday social. Sign language is used in the daily lives of people with hearing and speech impaired.Applications